2019
DOI: 10.1016/j.nicl.2019.102081
|View full text |Cite
|
Sign up to set email alerts
|

Common increased hippocampal volume but specific changes in functional connectivity in schizophrenia patients in remission and non-remission following electroconvulsive therapy: A preliminary study

Abstract: HighlightsElectroconvulsive therapy (ECT) induced enlargement in hippocampus volume contrast to pharmaceutical therapy in schizophrenia.Both ECT responders and non-responders show hippocampal volume expansion.Increased FC between hippocampus and brain cognitive networks only in ECT responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 56 publications
3
51
0
Order By: Relevance
“…Interestingly, we observed a significant increased pHippocampus–ICC connectivity during retrieval condition and this was found to be strongly associated with memory accuracy in schizophrenia. It is worth mentioning that connectivity alterations between hippocampal subregions and ICC have also been observed by other authors 31 , 54 . The ICC, including the primary visual cortex, is known to send projections to posterior parietal regions through the dorsal visual processing stream 74 76 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, we observed a significant increased pHippocampus–ICC connectivity during retrieval condition and this was found to be strongly associated with memory accuracy in schizophrenia. It is worth mentioning that connectivity alterations between hippocampal subregions and ICC have also been observed by other authors 31 , 54 . The ICC, including the primary visual cortex, is known to send projections to posterior parietal regions through the dorsal visual processing stream 74 76 .…”
Section: Discussionsupporting
confidence: 76%
“…In resting-state connectivity, the investigations performed thus far have shown deficits in functional connectivity mainly between the anterior hippocampus (aHippocampus) and DMN regions, such as the medial prefrontal cortex and the PCC 31 , 35 , 52 , 53 , as well as between the posterior hippocampus (pHippocampus) and the anterior cingulate cortex 31 , 35 , 52 , 53 . Alterations of connectivity between the aHippocampus and temporal regions 35 , 53 , 54 , as well as between the pHippocampus and the dorsolateral prefrontal cortex 54 , have also been observed, though less consistently. To our knowledge, only one task-based functional connectivity study has been published on hippocampal subregions in schizophrenia showing reduced connectivity from the posterior hippocampus to the inferior frontal gyrus during a complex working memory task 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Another group examined the effects of ECT on patients with schizophrenia (i.e., ECT+antipsychotic medication; n=21) compared with schizophrenia patients who did not receive ECT and underwent antipsychotic treatment only (n=21). [44][45][46] Whole-brain analyses showed increased GMVs in the bilateral parahippocampal gyri/hippocampi, right temporal pole/right superior temporal gyrus (STG), and right insula after ECT compared to baseline and the antipsychotics only group. 44 Additional ROI analyses of the insula and hippocampus indicated increased GMVs in the bilateral dorsal anterior insula and posterior insula 46 and bilaterally increased hippocampal volumes.…”
Section: Effect Of Ect On Brain Structuresmentioning
confidence: 99%
“…44 Additional ROI analyses of the insula and hippocampus indicated increased GMVs in the bilateral dorsal anterior insula and posterior insula 46 and bilaterally increased hippocampal volumes. 45 An analysis stratified according to response status to ECT further showed that higher baseline volumes in the left hippocampus-amygdala transition area (HATA) were observed in responders. 45 A separate study group reported that baseline GMVs in the temporal region, including the right insula, left middle temporal gyrus (MTG), and the right STG, along with the left inferior frontal gyrus (IFG), predicted ECT response.…”
Section: Effect Of Ect On Brain Structuresmentioning
confidence: 99%
“…Schizophrenia (Zheng et al, 2019), first episode and chronic disease (Kawano et al, 2015;McHugo et al, 2018), symptom correlates (Kühn et al, 2012;Han et al, 2016), first episode psychosis (Buchy et al, 2016;Baglivo et al, 2018;Li et al, 2018), response to electroconvulsive therapy (Jiang et al, 2019b), conversion of high risk patients (Provenzano et al, 2020), young relatives at risk (Francis et al, 2013;Ho et al, 2017a), progression patterns (Ho et al, 2017b), genetic and cognitive correlates of schizophrenia (Nakahara et al, 2019) Metacognition and insight deficits (Hýža et al, 2016;Orfei et al, 2017;Alkan et al, 2019),…”
Section: Schizophreniamentioning
confidence: 99%